2009
DOI: 10.1063/1.3176933
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of electrical charging effects for ferromagnetic Mn-doped ZnO nanocrystals embedded into a SiO2 layer fabricated by KrF excimer laser irradiation

Abstract: Growth optimization and structural analysis for ferromagnetic Mn-doped ZnO layers deposited by radio frequency magnetron sputtering J. Appl. Phys. 99, 113515 (2006); 10.1063/1.2200768Mn-doped ZnO and (Mn, Cu)-doped ZnO thin films: Does the Cu doping indeed play a key role in tuning the ferromagnetism?The ZnMnO nanocrystals were formed by the laser irradiation of the sputter-deposited ZnMnO ultrathin layer using a 248 nm KrF excimer laser, and the size and density of the nanocrystals were observed to be control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…This C-V behaviour is similar to MIS memories with floating gates based on CdSe NC embedded in SiO 2 [42]. Previous work on ZnO embedded in MIS capacitors performed by other groups [4,43] demonstrated that the flat band shift was <1.5 V. The flat band voltage shift obtained from our samples is larger than the previously reported one, which could be explained by the large concentration of NCs or a better retention system. Also notice that the C-V curves might be influenced by the defects at the NCs/Al 2 O 3 interface and even inside the ZnMnO NCs, which could also contribute to the voltage shift.…”
Section: Resultssupporting
confidence: 81%
“…This C-V behaviour is similar to MIS memories with floating gates based on CdSe NC embedded in SiO 2 [42]. Previous work on ZnO embedded in MIS capacitors performed by other groups [4,43] demonstrated that the flat band shift was <1.5 V. The flat band voltage shift obtained from our samples is larger than the previously reported one, which could be explained by the large concentration of NCs or a better retention system. Also notice that the C-V curves might be influenced by the defects at the NCs/Al 2 O 3 interface and even inside the ZnMnO NCs, which could also contribute to the voltage shift.…”
Section: Resultssupporting
confidence: 81%